2001
DOI: 10.1111/0038-4941.00011
|View full text |Cite
|
Sign up to set email alerts
|

A Double Disadvantage? Minority Group, Immigrant Status, and Underemployment in the United States

Abstract: Objective. This study documents the magnitude of four types of underemployment experienced by both native-born minority and ethnic immigrant male and female workers in the United States and tests a "double disadvantage" economic outcome hypothesis that minority workers tend to be channeled into secondarysector jobs and that immigrant workers face initial disadvantages in labor force assimilation. Method. Data for men and women aged 25-64 who are in the labor force and not attending school were derived from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(94 citation statements)
references
References 23 publications
2
91
0
1
Order By: Relevance
“…Social norms and values, associated with the industrial development and modernity of country of origin, denote family priorities and the role of women at work versus at home. As several studies have shown (De Jong and Madamba 2001;Raijman and Semyonov 1997;Reimers 1985), substantial interaction takes place between geocultural background and socio-demographic characteristics in relation to labor force activity in the new country. Immigrant women from less developed countries experience greater decline in labor-force participation than do their women counterparts from advanced industrial economies, although the differentials narrow as time in the host country increases.…”
Section: Theoretical Perspectivementioning
confidence: 98%
See 1 more Smart Citation
“…Social norms and values, associated with the industrial development and modernity of country of origin, denote family priorities and the role of women at work versus at home. As several studies have shown (De Jong and Madamba 2001;Raijman and Semyonov 1997;Reimers 1985), substantial interaction takes place between geocultural background and socio-demographic characteristics in relation to labor force activity in the new country. Immigrant women from less developed countries experience greater decline in labor-force participation than do their women counterparts from advanced industrial economies, although the differentials narrow as time in the host country increases.…”
Section: Theoretical Perspectivementioning
confidence: 98%
“…Up to my knowledge, less than a dozen studies have focused on gender gaps in employment status, or labor force participation, among recent immigrants (Baker and Benjamin 1997;Boyd 1984;Boyle et al 2001;Kats 1982) or observed differences across origin groups within a single country (Antecol 2000;De Jong and Madamba 2001;Raijman and Semyonov 1997). The findings of this research reveal considerable variations among immigrant groups and destination countries.…”
Section: Introductionmentioning
confidence: 99%
“…47,49 This investigation is the first-known study to examine cross-level interactions epidemiological studies. [50][51][52] For instance, people with disability who live outside major cities may fare worse than their counterparts living in major cities, or people with no disability who live outside major cities. 50 These findings suggest that while individual-and neighborhoodlevel socioeconomic disadvantage may affect physical function independently, they also interact with one another to impact physical function in a collective way.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Portanto, embora a imigração em muitos casos beneficie as elites, a classe média e a economia em geral -por exemplo, estimulando o comércio e o mercado imobiliário, e permitindo a continuação de atividades produtivas que de outra maneira teriam sido deslocadas para outros países -ela tende a prejudicar os trabalhadores mais pobres e os menos qualificados do país de acolhimento, sobretudo as minorias (Catanzarite, 2003;Cherry, 2003;Johannsson;Shulman, 2003;Mason, 2014). No caso dos Estados Unidos, as pesquisas geralmente se concentram nas consequências da imigração para a população negra, embora algumas pesquisas também focalizem os efeitos para os latinos (descendentes de latino-americanos) nascidos nos EUA ou para os imigrantes que chegaram em levas anteriores (Jong;Madamba, 2001;Cherry 2003;Hall;Farkas, 2008;Roth, 2012).…”
unclassified